Biografi Sejarah dan Pemikiran K.H. Muhammad Kurdi Mama Cibabat Cimahi (1839-1954) - Anjar, Ari; Hasbullah, Moefllich; Isana, Widiati (Historia Madania: Jurnal Ilmu Sejarah, 2018)
The intellectual treasury of the archipelago was colored by the existence of a network of thought of the religious elites of Islam. Ulama in the archipelago form a chain of teachers connected to scientific centers in various parts of the world. The interesting thing to look at is the creativity of the ulama in articulating the religious understanding which is gained through intellectual networks with a variety of local elements that form the various traditions of thought in the archipelago. This research is an attempt to uncover the style of thought of the local religious elites, within the framework of their traces and actions in social life. In addition, this research is expected to open a new horizon in the local ulama tradition discourse which is now forgotten. With the method of research within the history study, which is, heuristics, criticism, verification, and historiography, this study examines the religious elites in Sunda. K.H. Muhammad Kurdi is a local religious elite who pays high attention to the scientific tradition in the archipelago. His attention to science appears in abundant works and his appreciation of the translation of Arabic books into Sundanese. In this case, there are five parts of science that are the focus of K.H's thinking. Muhammad Kurdi. Among them are the translation of the Quran, the aqidah, fiqh, tasawuf, and sirah nabawiyah. In addition, the activity of K.H. Muhammad Kurdi in the field of da'wah included establishing the Pesantren Cibabat, leading the Tarekat Qadiriyah wa Naqsababandiyah, and becoming the Penghulu Besar (Hoefd-Penghulu) Bandung in 1946-1950.